Rice PcG gene OsEMF2b controls seed dormancy and seedling growth by regulating the expression of OsVP1. (July 2017) - Chen, Min; Xie, Shiyong; Ouyang, Yidan; Yao, Jialing
Highlights: Up or down regulation of OsEMF2b cause changes in grain size, weight and seed setting. Down regulation of OsEMF2b displayed reduced seed dormancy. OsEMF2b bound the promoter of OsVP1 and affected its H3K27me3 and H3K4me3 enrichment both in seed and seedling. Abstract: The induction and release of seed dormancy are a precisely regulated process that influences seed germination. ABA promotes seed dormancy but suppresses seed germination and seedling growth. However, how chromatin and epigenetic mechanisms regulate the expression of ABA related genes during these processes remains unclear. Polycomb gene OsEMF2b was required for regulation of seed dormancy and seedling growth by dynamically activating and repressing ABA signal response genes. Downregulation of OsEMF2b led to vivipary and decreased expression level of OsVP1, which was involved in ABA signal pathway in seed dormancy. While, the seedlings with downregulation of OsEMF2b exhibited hyper-sensitive response to ABA and the expression of OsVP1 is upregulated. Yeast one-hybrid assay and ChIP analyses proved that OsEMF2b could bind to the promoter of OsVP1 directly and affected H3K27me3 enrichments of OsVP1 in seedling. Interestingly, both H3K27me3 and H3K4me3 enrichments of OsVP1 were changed with OsEMF2b mis-expression in seed and seedling. We proposed that OsEMF2b may play a pivotal role in seed dormancy and seedling growth by regulating the expression of OsVP1 indirectly or directly.